Pemanfaatan Media Digital di Sekolah Dasar Pada Era Digital Native Generation - Eko Purnomo; Darmawati Darmawati; Rasmi Hi Panu (EDUKASI, 2025)
The utilization of digital learning media in the digital era is very important in order to motivate the Digital Native Generation. This study aims to determine the level of utilization of digital-based learning media in elementary schools in Ternate City. The method used in this research is descriptive quantitative with survey approach. The instruments used were questionnaires and interviews, the sample consisted of 141 teachers representing four sub-districts namely North Ternate, Central Ternate, South Ternate and West Ternate. The results showed that the utilization of digital learning media is still low. Most teachers teach using non-digital media such as textbooks, learning modules and teaching aids. Meanwhile, to evaluate learning teachers prefer to use educational games and written tests. This is due to limited technology facilities, limited application of digital learning media (e.g. laptop, infocus), student readiness, and teacher digital literacy being the main obstacles. In order for digital media integration to be well implemented, schools need to improve digital facilities in schools and digital literacy training for teachers to maximize digital media integration in learning.